Silver nanoparticles embedded hybrid organometallic complexes - Shahi, Praveen Kumar; Prakash, Rajiv; Rai, Shyam Bahadur (American Institute of Physics Inc., 2018)
A novel hybrid material comprising of two β-diketonate complexes, Tb(ASA)3Phen (TAP) and Eu(TTA)3Phen (ETP), has been synthesized and studied its photo-physics, energy transfer and optical thermometry applications. Using XRD and FTIR spectra, it has been demonstrated that both the complexes maintain their core entity and show weak interaction between them in the hybrid complex (HC). The TEM images show the coating of ETP layers over nano-fibrous TAP and further, embedded with Ag nanoparticles over HC. It has been observed that ligands (Phen, TTA as well as ASA) absorb the UV radiation and undergoes single to triplet via intersystem crossing transitions by transferring its excitation energy to central lanthanide ions (Eu3+ and Tb3+). In this strategy, an efficient energy transfer between two different species i.e. ASA to Tb3+ (in TAP complex) to Eu+3 ions (of ETP complex) has also been observed. To probe and verify the energy transfer mechanism, life time measurements have been carried out. The life time of Tb3+ decreases in HC as compared with TAP, whereas the life time of Eu3+ increases in HC as compared with ETP. The addition of silver nanoparticles (AgNPs) again enhances the fluorescence intensity of Eu3+ emission band. The prepared HC has further been demonstrated for ambient range temperature (295-365 K) sensing and the sensitivity of the material is found to be 6.8% change in signal per K. The strong optical property and non-toxic nature of this HC is useful in biomedical, bio-imaging and energy harvesting applications.
Structural interactions, photo-induced energy transfer, plasmonic effect and optical thermometry
Keywords: Silver nanoparticles; Embedded hybrid; Organometallic complexes; Structural interactions; Photo-induced energy transfer; Plasmonic effect and optical thermometry